Biotechnology in medical sciences - Khan, Firdos Alam (CRC Press, Taylor & Francis Group, 2014)
"This book is a comprehensive overview of all the important aspects of medical biotechnology intended for interested, scientifically oriented laypersons, along, who want a relatively low level presentation of important biotechnology medical specialties such as bacteriology, immunology, recombinant DNA, molecular diagnostics, gene therapy, synthetic biology, tissue engineering, bioethics, IP issues, vaccines, and more"--Resumé vydavatele